Overexpression mutants reveal a role for a chloroplast MPD protein in regulation of reactive oxygen species during chilling in Arabidopsis - Lunn, Daniel (Journal of experimental botany, 2022)
© The Author(s) 2022. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For permissions, please email: journals.permissionsoup.com.